2018
DOI: 10.1002/dvdy.24618
|View full text |Cite
|
Sign up to set email alerts
|

Loss of VAMP5 in mice results in duplication of the ureter and insufficient expansion of the lung

Abstract: VAMP5 KO mice showed a low birth rate and abnormalities of the urinary and respiratory systems. VAMP5 KO mice died around birth, possibly due to defects in vesicoureteral flow and breathing. The results presented could provide a basis for future studies to understand the roles of VAMP5 protein. Developmental Dynamics 247:754-762, 2018. © 2018 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Ubiquitin conjugating enzyme E2 L6 (UBE2L6) serves as an E2 enzyme for post-translational addition of an ubiquitin-like protein ISG15 which is vital for antiviral immunity ( Skaug and Chen, 2010 ) and is involved in the type-I interferon response in active TB disease ( Ottenhoff et al, 2012 ). Vesicle-associated membrane protein 5 (VAMP5) is a member of the SNARE protein family, which regulates the docking and fusion of intracellular membrane vesicles ( Hong, 2005 ) and is involved in the development or function of the respiratory system ( Ikezawa et al, 2018 ). VAMP5 controls intracellular transport events, including endocytosis, exocytosis, and internal recycling ( Tajika et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquitin conjugating enzyme E2 L6 (UBE2L6) serves as an E2 enzyme for post-translational addition of an ubiquitin-like protein ISG15 which is vital for antiviral immunity ( Skaug and Chen, 2010 ) and is involved in the type-I interferon response in active TB disease ( Ottenhoff et al, 2012 ). Vesicle-associated membrane protein 5 (VAMP5) is a member of the SNARE protein family, which regulates the docking and fusion of intracellular membrane vesicles ( Hong, 2005 ) and is involved in the development or function of the respiratory system ( Ikezawa et al, 2018 ). VAMP5 controls intracellular transport events, including endocytosis, exocytosis, and internal recycling ( Tajika et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…1d). Validity of the VAMP5 antibody (Supplementary Table 1) was indicated by the observation that VAMP5-deficient mice show strongly reduced signals in immunoblots and immunohistochemical staining performed with the same antibody (Ikezawa et al, 2018). Moreover, VAMP5 appeared as a top enriched protein in immunoprecipitated retinal lysates analysed by mass spectrometry (Supporting Data 1).…”
Section: Resultsmentioning
confidence: 99%
“…VAMP5 has also been shown to be part of the machinery that mediates EV-dependent cytokine release from 26 mesenchymal stem cells in vitro (Kou et al, 2018). VAMP5 did not mediate fusion of vesicular and plasma membrane containing specific tSNAREs in an artificial exocytosis assay (Hasan et al, 2010), but deletion of VAMP5 from mice causes developmental defects in the respiratory and urinary systems and perinatal death (Ikezawa et al, 2018). The observed upregulation of VAMP5 and the changes in CD9 distribution under ischemic conditions suggest that VAMP5 is part of the gliotic reaction to injury and disease and that ischemia affects EV secretion in the retina.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This correlation can add molecular data to the 3D morphological data, although the molecular data are limited to 2D distribution. To date, the CoMBI-C system has been used in various research fields, such as 3D analysis of primordia of beetle horn 16 , 3D distribution analysis of myelinated fibers of human facial nerves 17 , 3D morphological analysis of polycystic kidney of knockout mice 18 , and 3D visualization of regenerating bones and cartilage of the axolotl jaw 19 . Through these collaborative studies and ongoing collaborations, we found that users of the conventional CoMBI-C system desired compatibility with not only frozen specimens but also paraffin-embedded specimens.…”
Section: Introductionmentioning
confidence: 99%